Microfluidic harvesting of breast cancer tumor spheroid-derived extracellular vesicles from immobilized microgels for single-vesicle analysis. Issue 13 (17th May 2022) - Rima, Xilal Y.; Zhang, Jingjing; Nguyen, Luong T. H.; Rajasuriyar, Aaron; Yoon, Min Jin; Chiang, Chi-Ling; Walters, Nicole; Kwak, Kwang Joo; Lee, L. James; Reátegui, Eduardo
Abstract : A novel microfluidic system for the low-volume harvesting of extracellular vesicles from breast cancer tumor spheroids encapsulated within immobilized hydrogel microbioreactors for downstream single-vesicle analyses. Abstract : Investigating cellular and vesicular heterogeneity in breast cancer remains a challenge, which encourages the development of controllable in vitro systems that mimic the tumor microenvironment. Although three-dimensional cell culture better recapitulates the heterogeneity observed in tumor growth and extracellular vesicle (EV) biogenesis, the physiological relevance is often contrasted with the control offered by two-dimensional cell culture. Therefore, to challenge this misconception we developed a novel microfluidic system harboring highly tunable three-dimensional EV microbioreactors ( EV μBRs) to model micrometastatic EV release in breast cancer while capitalizing on the convenient, low-volume, and sterile interface provided by microfluidics. The diameter and cellular occupancy of the EV μBRs could be precisely tailored to various configurations, supporting the formation of breast cancer tumor spheroids. To immobilize the EV μBRs within a microchannel and facilitate EV extraction, oxygen inhibition in free-radical polymerization was repurposed to rapidly generate two-layer hydrodynamic traps in situ using a digital-micromirror device (DMD)-based ultraviolet (UV) projection system. Breast cancer tumor spheroid-derived EVs were harvested with as little as 20 μL from the microfluidic system and quantified by single-EV immunofluorescence for CD63 and CD81. Despite the low-volume extraction, differences in biomarker expression and coexpression of the tetraspanins on single EVs were observed. Furthermore, the EV μBRs were capable of recapitulating heterogeneity at a cellular and vesicular degree, indicating the utility and robustness of the microfluidic system to investigate physiologically relevant EVs in breast cancer and other disease models.